2081. Building a Decision Tree with Serial Serology Measurements Improves Classification in a Flavivirus Co-circulation Region - Lumbard, Keith; Arteaga Cabello, Fernando J; Gouel-Cheron, Aurelie; Belaunzarán, Francisco; Nájera-Cancino, Gabriel; Caballero-Sosa, Sandra; Rincón-León, Héctor; Del Carmen Ruis Hernandez, Emilia; Cervantes, Pilar Ramos; Lourdes Guerrero, M; Beigel, John; Trujillo-Murillo, Karina; et al. (Open forum infectious diseases, 2018)
Background RT-PCR (reverse transcriptase polymerase chain reaction) is often considered the “gold standard” for diagnosis of Zika Virus (ZIKV) infection; however, it has been shown to have low sensitivity. A possible remedy is to study ZIKV-specific IgG (ZsIgG) and IgM (ZsIgM) antibodies. However, the in vitro cross-reactivities of Dengue virus (DENV) and ZIKV-specific antibodies are well known, leading to diagnostic difficulties in an area with co-circulation of the two viruses. Our goal was to use Zika and Dengue serologic assays to build a classification model that improves upon the PPV of commercial kits while maintaining sensitivity. Methods We conducted a prospective longitudinal study in Southern Mexico where DENV and ZIKV co-circulation occurs (NCT02831699). Patients were included in two cohorts: a cohort of subjects presenting with a febrile rash meeting WHO/PAHO Zika case definition and a household cohort. After signed consent, all subjects enrolled were evaluated on study-visit Days 0, 3 and 7 (for fever rash cohort) and 28. We considered a subject “true positive” for ZIKV or DENV if RT-PCR positive at any time point. The healthy household cohort (with no positive RT-PCR) was considered “true negatives.” We fit a statistical decision tree taking as inputs serial serology measurements and outputting a predicted disease category. Funded in part by the NCI Contract No. HHSN261200800001E. Funded in part by the Mexican Ministry of Health. Results As of March 2018, we have 32 subjects in the Zika PCR+ group, 32 in the Dengue PCR+ group, and 68 in the household group. Our decision tree (Figure 1) achieved PPV of at least 90% on all three disease categories, while maintaining sensitivity above 50%. The highest PPV achieved by the kit manufacturer recommended cutoffs while maintaining a sensitivity of at least 10% on Zika PCR+ subjects is 30/114 (26%), and for Dengue PCR+ subjects is 21/30 (70%). Conclusion Using serology data in a statistical decision tree improves the PPV exhibited by the kit manufacturer recommendations while still maintaining respectable sensitivity. Physicians in regions with co-circulating flaviviruses should be aware of the pitfalls of using only RT-PCR or using pre-established commercial cutoffs in the serology kits for diagnosis. Disclosures All authors: No reported disclosures.